Impaired early‐phase suppression of glucagon secretion after glucose load is associated with insulin requirement during pregnancy in gestational diabetes. Issue 1 (2nd July 2019) - Horie, Ichiro; Haraguchi, Ai; Ito, Ayako; Nozaki, Aya; Natsuda, Shoko; Akazawa, Satoru; Mori, Yoshitaka; Ando, Takao; Higashijima, Ai; Hasegawa, Yuri; Yoshida, Atsushi; Miura, Kiyonori; et al.
Abstract: Aims/Introduction: The role of glucagon abnormality has recently been reported in type 2 diabetes; however, its role in gestational diabetes mellitus (GDM) is still unknown. The glucose intolerance in GDM is heterogeneous, and not all patients require insulin treatment during pregnancy. Here, we investigated whether glucagon abnormality is associated with the requirement for insulin treatment during pregnancy. Materials and Methods: A total of 49 pregnant women diagnosed with GDM were enrolled. They underwent a 75‐g oral glucose tolerance test during mid‐gestation, and we measured their plasma glucagon levels (by a new sandwich enzyme‐linked immunosorbent assay) at fasting (0 min), and at 30, 60 and 120 min after glucose load in addition to the levels of plasma glucose and serum insulin. All participants underwent another oral glucose tolerance test at postpartum. Results: Of the 49 patients, 15 required insulin treatment (Insulin group) and 34 were treated with diet therapy alone until delivery (Diet group). The early‐phase glucagon secretion after glucose load, as determined by the changes in glucagon from the baseline to 30 min, was paradoxically augmented during mid‐gestation in the Insulin group, but not in the Diet group. The impaired glucagon suppression during mid‐gestation in the Insulin group was not associated with insulin secretory/sensitivity indexes studied, and was ameliorated postpartum, although the plasma glucose levels remained higher in the Insulin group versus the Diet group. Conclusions: Impaired early‐phase suppression of glucagon could be associated with the requirement for insulin treatment during pregnancy in patients with GDM. Abstract : We evaluated the glucagon responses to oral glucose load in patients with gestational diabetes mellitus using a new sandwich enzyme‐linked immunosorbent assay. We investigated whether the glucagon abnormality is associated with the requirement for insulin treatment during pregnancy.